2013
DOI: 10.1242/jcs.124768
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of RAD17 sensitizes pancreatic cancer cells to gemcitabine

Abstract: SummaryChemotherapy of advanced pancreatic cancer has mainly been gemcitabine-based for the past 15 years, with only limited effect. Recently, combination therapy that also targets checkpoint kinase 1 (CHK1) has become an attractive option. The central role of CHK1 in many DNA-damage response pathways, however, may result in undesired cytotoxicity in normal cells, causing side effects. We were searching for other target molecules of similar function that may be more specific and thus better suited for combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 49 publications
3
24
0
2
Order By: Relevance
“…5C; 1-0-14 ), representing a synthetic lethal relationship of potential therapeutic relevance. Consistent with this finding in yeast, depletion of hRAD17 can sensitize pancreatic cancer cells to gemcitabine [74].…”
Section: Resultssupporting
confidence: 55%
“…5C; 1-0-14 ), representing a synthetic lethal relationship of potential therapeutic relevance. Consistent with this finding in yeast, depletion of hRAD17 can sensitize pancreatic cancer cells to gemcitabine [74].…”
Section: Resultssupporting
confidence: 55%
“…As expected, this signature is associated to B lymphocyte ontogeny and functions [e.g., “development of B lymphocytes” p  = 10 −10.4 , “antibody response” ( p  = 10 −7.5 ), “proliferation of B lymphocytes” ( p  = 10 −10.5 ), and “morphology of B lymphocytes” ( p  = 10 −7.5 ) as well as to the “B cell receptor signaling” pathway ( p  = 10 −7.3 )] (Figure 11B). The B cell signature also pinpoints to genes without any known function in B cells yet, such as the cell cycle gene RAD17 (53) or the SP140 gene that encodes a nuclear body protein (54) (Table 1). Altogether, the results of the functional analysis of the conserved signature of B cells support the biological relevance of the conserved gene signatures generated by our approach.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that Rad17 expression is elevated in colon carcinoma, breast cancer, pancreatic cancer, gastric cancer and non‐small‐cell lung cancer and is correlated with tumour cell onset and progression (Bao et al , ; Fredebohm et al , ; Wang et al , ). NELFA is an essential element of the NELF complex that negatively regulates the elongation of RNA polymerase II‐mediated transcription (Gilchrist et al , ; Jadlowsky et al , ; Stadelmayer et al , ).…”
Section: Discussionmentioning
confidence: 99%